Exogenous L-Serine Alleviates Pasteurella multocida-Induced Inflammation by Reprogramming the Transcription and Metabolism of Macrophages - Fang He; Zhengchun Lang; Yanlan Huang; Yangyang Qiu; Pan Xiong; Nengzhang Li; Guangfu Zhao; Yuanyi Peng (Veterinary Sciences)
P. multocida is notorious for inducing excessive inflammation with high lethality in multiple animals, such as cattle, pigs, and chickens. Our previous study revealed that L-serine was decreased in the lungs of mice infected with P. multocida capsular type A strain CQ2 (PmCQ2), and 2 mg/kg of L-serine could alleviate PmCQ2-induced lung inflammation in vivo, which may largely depend on macrophages. However, the underlying intrinsic alterations remain unknown. Here, we demonstrated that 10 mM of L-serine significantly inhibited the release of inflammatory cytokines (e.g., IL-1β and TNF-α) by blocking inflammasome activation (including NALP1, NLRP3, NLRC4, AIM2, and Caspase-1) in PmCQ2-infected macrophages. Furthermore, the results of RNA-seq and metabonomics revealed that exogenous L-serine supplementation substantially reprogrammed macrophage transcription and metabolism. Mechanically, L-serine reduced inflammatory responses via the inhibition of glycolysis in macrophages based on a seahorse assay. Together, these findings characterize the intrinsic molecular alterations in activated macrophages and provide new targets for modulating P. multocida infection-induced macrophage inflammation.